Fa'aliyah Istikhdam Namudzaj At-Ta'lim At-Ta'awuni Bi Nau'i Mu'adlilah Al-Kalimat Li Tarqiyah Isti'ab Al-Mufradat - J Sutarjo (Institut Agama Islam Negeri Metro, 2022)
The Arabic vocabulary has characteristics that distinguish it from other vocabulary, such as the exits of it's letters, meaning and derivations. Therefore, the teacher should use the supportive instructional model to gain vocabulary comprehension. The objective of this research is to find out the effectiveness of using the cooperative education model with the type of word dilemma in comprehending the vocabulary of the eighth grade students at Ma'arif 2 Islamic Junior High School Kota Gajah for the academic year 2020/2021 after using the cooperative education model with the type of word dilemma, and the kind of this research is qualitative research with the number of students are 20 persons. The data in this research was collected from indigenous organisms using the method of observation, test and document.